PTH-202 Evaluation of the percussive pop technique to restore patency to long term central venous catheters in patients on home parenteral nutrition. (22nd June 2015) - Small, M; Patel, S; Crowther, S
Abstract : Introduction: Functioning central venous catheters (CVC) are essential for the delivery of home parenteral nutrition (HPN). Occluded CVC result in delayed treatment and increased risk of infection. Various techniques to restore patency have been described in this patient group, however the percussive POP technique has not been evaluated. The POP technique generates shock waves through the CVC loosening the obstruction, allowing it to be extracted, rather than introduced into the patient. 1 This study aimed to evaluate the technique in patients on HPN. Method: Occlusions between January 2012 and December 2014 were recorded. Total occlusion indicated the CVC could not be flushed, partial indicated resistance. Techniques used to salvage the CVC and outcomes were recorded. 1st line techniques were clearing the hub of any physical matter with a 21G needle and POP technique where a 2.5 ml Luer lock syringe with 1ml 0.9% sodium chloride was attached directly to the CVC hub (tip pointing down). The plunger was then pulled up 1 ml and released. This was repeated until blood backflow or debris was seen in the syringe. 2nd line involved Urokinase 10, 000 units or 70% alcohol. Primary outcome was catheter salvage. Other outcomes were CVC rupture, "ballooning" (where the CVC becomes permanently stretched), bacteraemia or recurrence of occlusion within 30 days of intervention. Results: There were 39 occlusions (30 total, 9 partial) in 27 patients; occlusion rate 0.1 per 1000 CVC days. 25 patients had CVC, 2 patients ports. Patency was restored in 38 (97%) episodes. The 1 unsuccessful episode was a total occlusion in a port resistant to all methods. The 30 total occlusions occurred in 19 patients; 17 patients CVC, 2 patients port. Patency restored on 29 (97%) occasions. Hub clearout used in 5 (17%) episodes, in 2(7%) this was the only method used. POP technique used for 28 (93%) episodes, 3(10%) following hub clearout. Urokinase used in 4 (13%) episodes. In 2 cases patency was restored by the POP technique but with some residual resistance. Urokinase was instilled using the POP technique on 1 occasion. Alcohol was only used once and was unsuccessful. Of the 9 partial occlusions, patency was restored in all. Hub clearout alone was used in 7(78%) occasions. POP technique used in 2(22%) episodes and once with Urokinase (11%). There were no catheter ruptures, "ballooning" or bacteraemia. There was 1 recurrence of total occlusion in a patient on a trial off HPN who was non compliant with weekly CVC flushing. Conclusion: The results indicate that restoring patency using the percussive POP technique is safe and effective. In addition, it is simple and inexpensive. Urokinase may have an additional role alongside non pharmaceutical methods, but is not often required. Disclosure of interest: None Declared. Reference: Stewart D. Care of the critically ill 2001;17(3)